(untitled) (Communications in Computational Physics, 2018)
In this study long bubble rising in a narrow channel was investigated using multiphase lattice Boltzmann method. The problem is known as a Bretherton or Taylor bubble flow [2] and is used here to verify the performance of the scheme proposed by [13]. The scheme is modified by incorporation of multiple relaxation time (MRT) collision scheme according to the original suggestion of the author. The purpose is to improve the stability of the method. The numerical simulation results show a good agreement with analytic solution provided by [2]. Moreover, the convergence study demonstrates that the method achieves more than the first order of convergence. The paper also investigates the influence of simulation parameters on the interface resolution and shape.